Prevalence of neuropathic pain in the foot and ankle patients. Issue 3 (14th September 2018) - Sidon, Eliezer; McDonald, Elizabeth; Daecher, Annemarie; Shakked, Rachel; Pedowitz, David; Daniel, Joseph; Winters, Brian; Raikin, Steven
Category: Other Introduction/Purpose: The management of pain in patients with foot and ankle pain can be challenging. Cumulative data suggest that, in addition to nociceptive mechanisms, other neuropathic mechanisms can contribute to pain in a subset of people with osteoarthritis. Neuropathic mechanism include central sensitization or peripheral neuropathic hyper activated pain. Heterogeneous pain mechanisms may explain variable responses to recommended pain therapies. Accurate classification of pain phenotype using clinically feasible tools has potential to improve pain management. The PainDETECT score, a validated patient-report questionnaire was developed to identify neuropathic pain. A recent study found a prevalence of 23% of neuropathic pain following ORIF of Ankle fractures. The purpose of this study is to examine the prevalence of neuropathic pain (NP) in a variety of foot and ankle disorders. Methods: This is a cross-sectional study investigating the prevalence of NP in a population of patients undergoing foot and ankle surgery. The patient cohort will include 500 patients. Patients were prospectively reviewed, prior to their surgery, using a patient-self-report questionnaire (painDETECT). Patients' demographics, diagnosis, comorbidities and functional scores were also prospectively collected. painDETECT score of less than 13 was considered as Nociceptive, score of more than 18 was considered as Neuropathic. Scores of 12 to 18 were considered as Unclear. ANOVA and Student's t-tests were performed to compare the pain VAS scores, duration of pain prior to surgery, severity of the disease and the prevalence of NP, and among different foot and ankle procedures (bone versus tissue, elective versus trauma) and procedural regions (hindfoot/ankle, midfoot, forefoot). Results: A total of 116 patients were included in this preliminary study. 9 patients (7.7%) were diagnosed with neuropathic pain and 24 (20.6%) were Unclear according to their results in the painDETECT. There were 28 patients scheduled for surgery due to recent trauma, none of which had neuropathic pain. One patient with neuropathic pain was scheduled for excision of Morton's neuroma and 2 patients for removal of foreign body or hardware. There was no significant correlation with age, BMI or smoking status nor with the patients' functional scores. Patients with NP described their worst and current level of pain significantly higher than those with nociceptive pain. (9.4 Vs 7.4 for worst pain and 6.9 Vs 4.6 for current level in a scale from 0-10, p-value<0.05). Conclusion: A considerable number of the patients with foot and ankle problems requiring surgeries also has pain of a neuropathic mechanism. It is more common in chronic pain than in trauma. This should be evaluated pre-op and taken into attention when deciding on a surgical intervention or pain management.